Association of Age-adjusted Charlson Comorbidity Index With Orbital Fungal Disease Outcomes. Issue 1 (4th June 2021) - Kupcha, Anna C.; Simmons, Brittany A.; Law, James J.; Liu, Yuhan; Chen, Qingxia; Shriver, Erin M.; Brown, Eric N.; Mawn, Louise A.
Abstract : Purpose: To determine whether the age-adjusted Charlson comorbidity index (age-CCI) in sino-orbital fungal disease patients correlates with disease-specific mortality. Methods: Hospital billing systems at 2 academic institutions were queried for patients with ICD-9, ICD-10, and CPT codes used in fungal disease who also had orbital disease and significant visual loss. Thirty-two patients at Institution A and 18 patients at Institution B met the inclusion criteria of microbiologic or pathologic confirmation of fungal infection and completion of inpatient ophthalmology evaluation. Patients without radiographic abnormality in the sinus or orbit were excluded. Demographic, diagnostic, treatment, and outcome variables were recorded. Our primary outcome was death due to fungal disease. Results: Of the 50 medical records examined, 44 patients met the criteria for fungal-related death outcome on multivariate analysis. The regression coefficient for age-CCI and fungal-related mortality was 0.242 (95% CI, 0.012–0.779) with a p value of 0.038. Conclusions: Age-CCI is significantly associated with fungal-related mortality. This relationship remains significant when controlling for 5 covariates of fungal organism phylum, presence or absence of CNS disease, exenteration, local treatment use, and presence or absence of an immunosuppressive diagnosis. Age-CCI shows promise as a clinical and research tool in the evaluation of invasive fungal disease involving the orbit. Abstract : In a retrospective study at 2 institutions, the authors demonstrate that age-adjusted Charlson Comorbidity Index is associated with disease-related mortality in invasive orbital fungal disease. Supplemental Digital Content is available in the text.